Optimization of Automatic Synthesis and Separation of [18F] AV-45 and Quality Control - Zhang, Qi-Zhou; Li, Yu-Bin; Yilihamu, Nazi; Li, Xiao-Hong; Ba, Ya; Qin, Yong-De (Frontiers in Chemistry, 2022)
Objective: Based on the Tracerlab FXF-N platform, a synthesis program and preparative high-performance liquid chromatography (HPLC) purification program edited by us can stably and repeatedly produce [18F] AV-45 without changing the process. The [18F] AV-45 produced meets the main indexes of radiopharmaceutical intravenous preparations. Methods: The O-toluene sulfonated precursor (1 mg) was subjected to nucleophilic radiofluorination at 115°C in anhydrous dimethyl sulfoxide (DMSO), then the protective group was hydrolyzed by acid. The neutralized reaction mixture was purified through a preparative HPLC then formulated for injection using a C18 purification cartridge. This method yielded a relatively pure [18F] AV-45 product with high specific activity. Results: Four consecutive radiochemical synthesis operations were carried out in this experiment; the average production time of [18F] AV-45 preparation was 60 min, the radiochemical yield was 14.8 ± 2.1% (n = 4), the radiochemical purity was greater than 95%, and the other important quality control indexes met the requirements of radioactive drugs for intravenous administration. Conclusion: This experiment was based on the Tracerlab FXF-N platform with the synthesis program and preparative HPLC purification program edited by us. Through screening and optimization of the separation and purification system and the separation and analysis system, as well as automatic radiochemical synthesis and preparation quality control, intravenous [18F] AV-45 was successfully prepared.